2007
DOI: 10.1073/pnas.0700118104
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent cross-talk between the transforming growth factor-β and interleukin-1 signaling pathways

Abstract: Some tumor cell lines secrete high concentrations of TGF␤ or IL-1. Similarly high concentrations of each of these cytokines cross-activate the other pathway: TGF␤ activates NFB, and IL-1␤ activates Smads. The IL-1 signaling components IRAK, MyD88, TRAF6, and TAK1 are all required for cross-activation of NFB by TGF␤. Knockdown experiments revealed that both TGF␤ receptor subunits are required for IL-1␤ to activate Smads, and the IL-1 receptor is required for TGF␤ to activate NFB. Coimmunoprecipitations showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 36 publications
5
80
0
Order By: Relevance
“…This effect was reported to be SMAD independent, proven by the fact that TRAF6 knockdown does not lead to activation of a TGFβ-responsive reporter (39). Finally, it was shown that the stimulation of cells with IL-1β leads in many cases to phosphorylation of SMAD2 and subsequent target gene activation (40). Taken together, our and other observations indicate the existence of cross-talk between two important cellular signaling pathways involved in immunity and other processes.…”
Section: Irak2 and Smad2: Connecting Il-1 And Tgfβ Signalingsupporting
confidence: 56%
“…This effect was reported to be SMAD independent, proven by the fact that TRAF6 knockdown does not lead to activation of a TGFβ-responsive reporter (39). Finally, it was shown that the stimulation of cells with IL-1β leads in many cases to phosphorylation of SMAD2 and subsequent target gene activation (40). Taken together, our and other observations indicate the existence of cross-talk between two important cellular signaling pathways involved in immunity and other processes.…”
Section: Irak2 and Smad2: Connecting Il-1 And Tgfβ Signalingsupporting
confidence: 56%
“…NF-nB activity has been associated with EMT and metastasis in breast cancer (29). Furthermore, autocrine TGF-h2 has been shown to activate NF-nB in cancer cells (14,16,30). Therefore, we used an NF-nB responsive promoter to examine NF-nB activity in the cells lacking ThRIII.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Moreover, there are several points of cross-talk between signaling pathways activated by TGF-β1 and IL-1β (Lu et al, 2007), thus their combined use provides a more physiological analysis for specific biological responses.…”
Section: Discussionmentioning
confidence: 99%